2014
DOI: 10.1097/igc.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Ovarian and Endometrial Cancer—an International Multicenter Case-Control Study

Abstract: Prognosis of patients with SEOC tended to be the same in comparison with matched controls with either one EC or OC. Therefore, it could be considered that patients with SEOC may be eligible for clinical trials of the advanced tumor component if no additional therapy is indicated for the other component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
2
39
0
3
Order By: Relevance
“…However, this study does not support this finding; following adjustment for histological type and stage, the prognosis was not remarkably different between SEOC and EOC in the early stages. This is in agreement with the results of an international multicentric case-control study [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, this study does not support this finding; following adjustment for histological type and stage, the prognosis was not remarkably different between SEOC and EOC in the early stages. This is in agreement with the results of an international multicentric case-control study [19].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, no genetic testing was performed. As indicated in many studies, it is unlikely that patients with synchronous primary cancers have hereditary cancer syndromes [19,26,27].…”
Section: Discussionmentioning
confidence: 98%
“…An international multicenter study has suggested that adjuvant treatment recommendations for SCEO should consider the risk of relapse of individual tumor component, and carboplatin and paclitaxel should be used as CT regimen, and if the endometrial component of SCEO is advanced, radiation therapy should be given subsequently to CT. 22 Chiang et al 13 found no significant impact of adjuvant therapy on survival on patients with SCEO. However, Ayhan et al 18 suggested that adjuvant therapy should be given to patients with SCEO to improve survival.…”
Section: Discussionmentioning
confidence: 97%
“…2,18,21 In an international multicenter study after adjusting factors that might influence survival such as age, disease stage, histology, tumor grade, and residual tumor after surgery, 77 patients with SCEO, 132 patients with primary endometrial cancer, and 126 patients with primary ovarian cancer were compared, and results showed that 5-year OS rates did not differ between groups (71.6%, 79.8%, and 69.3%, respectively). 22 They suggested that postoperative treatment recommendations for SCEO should consider the risk of relapse of the respective tumor compound, and carboplatin and paclitaxel should be used as CT regimen. 22 They also suggested if an endometrial component of the SCEO is advanced, then RT could be given subsequently to CT. 22 A population-based assessment of more than 1500 patients with SCEO showed that younger age at diagnosis, earlier stage, and better grade of disease are favorable characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…22 They suggested that postoperative treatment recommendations for SCEO should consider the risk of relapse of the respective tumor compound, and carboplatin and paclitaxel should be used as CT regimen. 22 They also suggested if an endometrial component of the SCEO is advanced, then RT could be given subsequently to CT. 22 A population-based assessment of more than 1500 patients with SCEO showed that younger age at diagnosis, earlier stage, and better grade of disease are favorable characteristics. 23 In our study, age younger than 55 years, premenopausal status, performing lymphadenectomy, absence of omental metastasis, and absence of residual disease were found to be significant prognostic factors in univariate analysis (Table 5).…”
Section: Discussionmentioning
confidence: 99%